Pengaruh Brand Ambassador dan Kualitas Produk terhadap Keputusan Pembelian Produk Lemonilo - Siti Maryam Bolen; Ratnawaty Marginingsih (Universitas 17 Agustus 1945 Semarang, 2024)
Market competition makes companies must be able to innovate in order to compete with other companies. Brand Ambassadors who have a positive image and good product quality can attract consumers and increase the purchase decision of a product to be marketed. This research was conducted with the aim of finding out the influence of Brand Ambassador and product quality on purchasing decisions. The method used in this study is a quantitative research method using research aids in the form of a questionnaire containing 7 questions about NCT Dream as a lemonilo Brand Ambassador, 8 questions about the quality of lemonilo products, and 7 questions about consumer purchase decisions disseminated through the researcher's social media. Based on the results of a questionnaire of 110 respondents, it can be concluded that the use of Brand Ambassadors who have a positive image and good product quality greatly affects the level of consumer purchase decisions. This research is expected to be an analysis material for the Company in placing a good strategy in market competition